The use of interval‐compressed chemotherapy with the addition of vincristine, irinotecan, and temozolomide for pediatric patients with newly diagnosed desmoplastic small round cell tumor. Issue 10 (19th July 2020) - Liu, Kevin X.; Collins, Natalie B.; Greenzang, Katie A.; Furutani, Elissa; Campbell, Kevin; Groves, Andrew; Mullen, Elizabeth A.; Shusterman, Suzanne; Spidle, Jennifer; Marcus, Karen J.; Weil, Brent R.; Weldon, Christopher B.; et al.
Abstract: Background: Desmoplastic small round cell tumor (DSRCT) is a rare aggressive sarcoma that affects children and young adults, and portends poor outcomes despite intensive multimodal treatment approaches. We report toxicity, response, and outcomes of patients with DSRCT treated with the addition of vincristine, irinotecan, and temozolomide (VIT) to interval‐compressed chemotherapy as per Children's Oncology Group ARST08P1. Methods: All newly diagnosed pediatric patients with DSRCT treated at Dana‐Farber Cancer Institute and Boston Children's Hospital between 2014 and 2019 as per ARST08P1, Arm P2 with replacement of VAC cycles with VIT, were identified. Medical records were reviewed for clinical and disease characteristics, and treatment response and outcomes. Results: Six patients were treated as per the above regimen. Median age at diagnosis was 15.1 years (range 3.2‐16.4) and five patients were male. Five patients had abdominal primary tumors, of which one had exclusively intraabdominal and four had extraabdominal metastases. Two initial cycles of VIT were well tolerated with nausea, vomiting, diarrhea, and constipation as the most common adverse events. Overall response rate defined as partial or complete response after two initial cycles of VIT was 50%. For local control, all patients had surgical resection followed by radiotherapy, and two patients received hyperthermic intraperitoneal chemotherapy at the time of surgery. Of the four patients who have completed therapy to date, three remain disease‐free with median follow‐up time of 46.7 months. Conclusions: The addition of VIT to interval‐compressed chemotherapy is tolerable and active in DSRCT, with activity warranting additional investigation.